2019
DOI: 10.1088/1361-648x/ab577a
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a charged neighboring particle on Förster resonance energy transfer (FRET)

Abstract: Förster resonance energy transfer (FRET) is an important physical phenomenon which demands precise control over the FRET rate for its wide range of applications. Hence, enhancing the FRET rate using different techniques has been extensively studied in the literature. Research indicates that introducing additional particles to a system consisting of a donor-acceptor pair can change the behaviour of FRET in the system. One such technique is to utilize the collective oscillations of the surface electrons of a nei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 81 publications
0
5
0
Order By: Relevance
“…Although it is currently possible to quantitatively estimate the EET rate constant, it is not necessarily clear which physical and chemical factors contribute to it and to which extent. Thus, despite being quantitatively accurate, it remains difficult to extract a precise microscopic picture suitable, for instance, to unravel at a molecular level, the experimental investigation aimed at controlling the energy transfer dynamics of a Förster resonance energy transfer (FRET) for a coupled pair of chromophores embedded in a tunable sub-wavelength Fabry-Pérot resonator [77] or for enhancing the FRET rate in several FRET-based applications [78]. Regarding the specific context of photosynthesis, a variety of EET theoretical formulations have been applied to study this process in pigments, and this is the case of C-PCs [79][80][81][82][83].…”
Section: Introductionmentioning
confidence: 99%
“…Although it is currently possible to quantitatively estimate the EET rate constant, it is not necessarily clear which physical and chemical factors contribute to it and to which extent. Thus, despite being quantitatively accurate, it remains difficult to extract a precise microscopic picture suitable, for instance, to unravel at a molecular level, the experimental investigation aimed at controlling the energy transfer dynamics of a Förster resonance energy transfer (FRET) for a coupled pair of chromophores embedded in a tunable sub-wavelength Fabry-Pérot resonator [77] or for enhancing the FRET rate in several FRET-based applications [78]. Regarding the specific context of photosynthesis, a variety of EET theoretical formulations have been applied to study this process in pigments, and this is the case of C-PCs [79][80][81][82][83].…”
Section: Introductionmentioning
confidence: 99%
“…A given SDF encodes all the information of the magnitude of the interaction strength as well as the time scales of the interactions. If the influence of the environment is strong compared to the electronic coupling between system sites, excitations are localized and the resultant transfer is incoherent, the dynamics of which can be fully analysed by Förster theory [15,23,24]. On the other hand, a weak system-bath coupling parameter leads to a Redfield or Lindblad type quantum master equation [25] and ensuing energy transfer falls under the coherent regime.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that strongly coupled systems can be utilized for nonradiative energy transport with the use of excitons in plasmonic systems [20]. Unlike the short distances supported by Förster and Dexter resonance energy transfer methods [21] that operates on dipole-dipole interactions, strong coupling mediated exciton energy transfer has demonstrated to transport energy to much larger distances. It has been shown that these distances can reach up to the extent of the polariton modes [22] and also the energy exchange can occur between spatially separated molecules [23].…”
Section: Introductionmentioning
confidence: 99%